An organic acid-modified 4-NP reaction catalyst and its preparation method and application

By introducing organic carboxylic acids into CuO-NiCo-LDH catalysts, CuO-A-NiCo-LDH is solved, and the catalytic activity and catalytic reduction are significantly improved. performance.

CN117920345BActive Publication Date: 2024-12-20CHINA WEST NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311722356.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-14
Publication Date
2024-12-20
Estimated Expiration
2043-12-14

AI Technical Summary

Technical Problem

The catalytic performance of existing CuO-NiO bimetallic materials in catalyzing 4-nitrophenol (4-NP) is not ideal enough and needs further improvement.

Method used

Using the method of organic weak acid modification, CuO-NiCo-LDH catalyst is prepared by ultrasonic assistance by using CuO, ZIF-67 and nitrate as raw materials, and organic carboxylic acid is introduced during the preparation process to form CuO-A-NiCo-LDH Catalysts to enhance catalytic activity.

Benefits of technology

The catalytic activity of the catalyst on 4-NP was significantly improved, and the catalytic activity was increased by nearly 1 times. The pseudo-first-order kinetic constant of the catalyst was increased from 0.2521min-1 to 0.5357min-1, which significantly accelerated the rate of electron release of NaBH4 and increased the catalytic reduction performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117920345B_ABST
    Figure CN117920345B_ABST
Patent Text Reader

Abstract

The invention discloses an organic acid-modified 4-NP reaction catalyst, a preparation method and an application thereof, and relates to the technical field of 4-nitrophenol reaction removal catalyst. CuO, ZIF-67 and nickel nitrate with a mass ratio of 1:0.6-4:4-25 are used as raw materials, and CuO-NiCo-LDH is obtained by ultrasonic assistance. An organic carboxylic acid is introduced during the preparation of CuO-NiCo-LDH to form CuO-A-NiCo-LDH, which is a 4-nitrophenol reaction catalyst, wherein A represents an organic carboxylic acid, and the molar ratio of the organic carboxylic acid to CuO is 1-5:1. The present invention can be seen from the catalytic reduction performance test results that the composite catalyst obtained by organic carboxylic acid modification has excellent catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of 4-nitrophenol reaction removal catalyst, and in particular to an organic acid-modified 4-NP reaction catalyst and a preparation method and application thereof. Background Art

[0002] 4-Nitrophenol (4-NP), as an important raw material for organic synthesis, is widely used in chemical production. However, 4-NP waste contained in chemical production poses a potential hazard to the ecosystem and human health. How to green and efficiently manage 4-NP in the environment and find scientific and effective means to remove residual 4-NP-type environmental pollutants in the environment are of great practical significance. At present, among the many methods for eliminating 4-NP in water, catalytic hydrogenation reduction is considered to be a very promising method due to its advantages such as simple operation, mild reaction conditions and high efficiency. The key to this method is to construct a catalyst with excellent catalytic performance and stability.

[0003] At present, the catalysts used for catalytic reduction of 4-NP mainly include three categories: precious metals, non-precious metals and carbon materials. The unique physical and chemical properties of copper and its derivatives show excellent catalytic activity in the reduction reaction of nitrophenol compounds. For example, Lv H et al. in the article "Electrospun Foamlike NiO / CuO Nanocomposites with SuperiorCatalytic Activity toward the Reduction of 4-Nitrophenol" and Ramu AG et al. in the article "A facile and green synthesis of CuO / NiO nanoparticles and their removalactivity of toxic nitro compounds in aqueous medium" mentioned the use of CuO-NiO bimetallic oxides for catalytic reduction of 4-NP. Metal organic frameworks (MOFs) are composed of transition metal cations and organic ligands, and have the characteristics of large specific surface area, easy-to-control structure, ordered pore structure, unsaturated and uniformly dispersed metal ions and coordination centers. Thanks to these structural characteristics of MOFs materials, MOFs materials are considered to be ideal precursors for the synthesis of nanoscale bimetallic oxides. Therefore, MOFs CuO-NiO bimetallic materials are expected to achieve efficient catalytic reduction of 4-NP. However, in our study, we found that the pseudo-first-order kinetic constant k for the catalytic reduction of 4-NP by CuO1 / NiO1, which has the best performance among MOFs CuO-NiO bimetallic materials, is 0.2792 min. -1 , mass normalization constant km =5.58×10 -2 min -1 μg -1 , which needs further improvement.

[0004] Layered double hydroxides (LDHs), also known as aluminum hydroxide-like compounds or anionic clays, can be expressed by the general formula: [M 2+ 1-x M 3+ x (OH)2] x+ [(A n- ) x / n ] x-. mH2O. Among them, M 2+ (Divalent metal cations, such as Zn 2+ , Cu 2+ and Mg 2+ etc.) and M 3+ (Trivalent metal ions, such as Al 3+ , Fe 3+ and Co 3+ etc.) constitute the host layer, A n- It is an anion in the interlayer channel, which is used to balance the positive charge of the host layer to make LDHs electrically neutral and plays a dominant role in the overall structure of LDHs. In addition, the stoichiometric coefficient x in the formula has a wide range of variation, thus producing a series of two-dimensional layered materials with adjustable composition, bronze-like layers and anion intercalations. The intralayer binding force of LDHs is very strong, and the interlayer interaction is very weak. Its two-dimensional sheet structure is anisotropic, with a thickness ranging from only one to a few atoms, and a lateral size between submicron and micron. These structural features give LDHs the advantages of high atomic exposure rate and large specific surface area, promoting its potential application in the field of catalysis. However, when we use LDHs as a dispersed carrier of nano-CuO, alleviate the agglomeration of CuO nanoparticles, increase the specific surface area of ​​the catalyst and enhance the adsorption of substrate molecules, and then obtain the CuO / NiCo-LDH target catalyst with the assistance of ultrasound: CuO 0.03 / NiCo-LDH, under the same reaction conditions, CuO 0.03 / NiCo-LDH(k=0.2521min -1 ) has a higher catalytic activity towards 4-NP than CuO1 / NiO1 (k=0.2792min -1 )'s catalytic activity towards 4-NP is still slightly low, which shows that further research is needed to further improve the catalytic activity of the catalyst towards 4-NP. Summary of the invention

[0005] In view of the above problems in the prior art, the present invention provides an organic acid-modified 4-NP reaction catalyst and a preparation method and application thereof, so as to further improve the catalytic performance of the CuO-NiO bimetallic material in catalytic reduction of 4-NP, so as to solve the technical problem that the catalytic performance of the existing CuO-NiO bimetallic material in catalytic reduction of 4-NP is not ideal enough.

[0006] The technical solution adopted by the present invention is as follows:

[0007] The invention discloses an organic weak acid modified 4-nitrophenol reaction catalyst. The invention uses CuO, ZIF-67 and nickel nitrate in a mass ratio of 1:0.6-4:4-25 as raw materials, and then obtains CuO-NiCo-LDH by ultrasound assistance. In the preparation process of CuO-NiCo-LDH, an organic carboxylic acid is introduced to form CuO-A-NiCo-LDH, which is the 4-nitrophenol reaction catalyst. A represents an organic carboxylic acid, and the molar ratio of the organic carboxylic acid to CuO is 1-5:1.

[0008] Preferably, the organic carboxylic acid is one or more of gallic acid, citric acid and tartaric acid.

[0009] More preferably, the organic carboxylic acid is tartaric acid, and the mass ratio of CuO, ZIF-67 and nickel nitrate is 1:1.16:7.95, and the molar ratio of tartaric acid to CuO is 1:1.25.

[0010] A method for preparing a 4-nitrophenol reaction catalyst modified by an organic weak acid comprises the following steps:

[0011] (1) CuO and ZIF-67 are placed in anhydrous ethanol respectively, and ultrasonically homogenized to obtain solution 1 for later use;

[0012] (2) Ni(NO3)2·6H2O is placed in anhydrous ethanol to obtain solution 2 for later use;

[0013] (3) Under stirring, solution 2 is transferred into solution 1, and an organic carboxylic acid is added. After stirring evenly, ultrasonic treatment is performed for 30 to 60 minutes. After the ultrasonic treatment is completed, the sample is collected by centrifugation, washed with deionized water, and finally vacuum dried to obtain CuO-A-NiCo-LDH.

[0014] Furthermore, the preparation process of CuO is as follows: adding Cu(Ac)2·H2O and 2,5-dihydroxyterephthalic acid in a molar ratio of 1.5:1 to a mixed solution of DMF and H2O in a volume ratio of 1.5:1, ultrasonically homogenizing, reacting at 100-150°C for 10-24h, collecting the product after the reaction by centrifugation, washing with methanol and freeze-drying, and then calcining the dried product at 400-450°C for 1-4h to obtain CuO.

[0015] Furthermore, the preparation process of ZIF-67 is as follows: 2-methylimidazole and Co(NO3)2·6H2O are respectively dissolved in methanol and ultrasonically homogenized, then the 2-methylimidazole solution is transferred into the Co(NO3)2·6H2O solution, and after continuous stirring for 4 hours, the ZIF-67 precipitate is collected by centrifugation and dried to obtain ZIF-67.

[0016] Furthermore, the mass ratio of the 2-methylimidazole to Co(NO3)2·6H2O is 2-2.5:1.

[0017] The organic acid-modified 4-NP reaction catalyst is used as a catalyst in a reaction of decomposing 4-NP using NaBH4 as a reducing agent.

[0018] In summary, compared with the prior art, the present invention has the following advantages and beneficial effects:

[0019] The present invention successfully prepared the organic carboxylic acid modified CuO / NiCo-LDH composite catalyst by hydrothermal, calcination and ultrasound-assisted method. On the one hand, it is to promote the hydrolysis of NaBH4 and release electrons from NaBH4 to increase the electron density in the reaction system; on the other hand, it is to intentionally form an active interface between CuO and NiCo-LDH to accelerate the transfer rate of electrons released by NaBH4 to 4-NP, and from CuO x / A y -The test results of the catalytic reduction performance of NiCo-LDH and its intermediates on 4-NP show that the composite catalyst modified by organic carboxylic acid has excellent catalytic activity, which is nearly 1 times higher than that of CuO-NiO bimetallic material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The catalytic performance diagram of each catalyst before acid modification, where (ae) are CuO, NiCo-LDH and CuO x UV-vis spectra of 4-NP catalytic reduction by CuO / NiCo-LDH; (f) UV-vis spectra of 4-NP catalytic reduction by CuO, NiCo-LDH and CuO x / NiCo-LDH catalytic reduction of ln(C t / C0) vs. t;

[0021] Figure 2 The catalytic performance diagram of each catalyst after acid modification, where (ab) are CuO 0.03 / NiCo-LDH、CuO 0.03 / A 0.3 -NiCo-LDH catalyzed reduction of C t / C0 and ln(Ct / C0) and t, (cd) are CuO 0.03 / TA y -NiCo-LDH catalyzed reduction of C t / C0 and ln(C t / C0) vs. t;

[0022] Figure 3 CuO 0.03 / TA 0.3 -NiCo-LDH(ab) catalytic reduction of C of 4-NP at different NaBH4 / 4-NP molar ratios t / C0 and ln(C t / C0) versus t and (cd) the C of 4-NP catalytic reduction at different 4-NP concentrations t / C0 and ln(C t / C0) vs. t;

[0023] Figure 4 CuO at different temperatures 0.03 / TA 0.3 - Experimental diagram of the catalytic activity of NiCo-LDH in catalytic reduction of 4-NP; (a) CuO 0.03 / TA 0.3 -Conversion diagram of catalytic reduction of 4-NP by NiCo-LDH, (b) pseudo-first-order kinetics, (c) Arrhenius plot and (d) Eyring-Polanyi plot;

[0024] Figure 5 CuO 0.03 / TA 0.3 - Cyclic stability experimental diagram of NiCo-LDH, where (a) CuO 0.03 / TA 0.3 - Recyclability bar graph of 4-NP catalytic reduction by NiCo-LDH; (b) CuO, NiCo-LDH, CuO 0.03 / NiCo-LDH and CuO 0.03 / TA 0.3 -Nyquist plot of NiCo-LDH;

[0025] Figure 6 CuO 0.03 / TA 0.3 -(ac) SEM images and (d) EDS images of NiCo-LDH;

[0026] Figure 7 CuO 0.03 / TA 0.3-Element distribution map of NiCo-LDH;

[0027] Figure 8 (ac)XRD patterns and (de)FT-IR patterns of the target catalyst and its precursor;

[0028] Fig. 9 CuO 0.03 / TA 0.3 -XPS spectrum analysis of NiCo-LDH, including (a) total spectrum, (b) C 1s, (c) O1s, (d) Cu 2p, (e) Ni 2p and (f) Co 2p;

[0029] Fig.10 CuO, NiCo-LDH, TA 0.3 -NiCo-LDH, CuO 0.03 / NiCo-LDH and CuO 0.03 / TA 0.3 -(a) N2 adsorption-desorption isotherm and (b) pore size distribution curve of NiCo-LDH. DETAILED DESCRIPTION

[0030] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.

[0031] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0032] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0033] The present application will be described in detail below with reference to embodiments and experimental data.

[0034] Example 1

[0035] 1. Prepare each reagent as follows:

[0036] Preparation of Cu-MOF-74: 0.0749g (0.375mmol) Cu(Ac)2·H2O and 0.0495g (0.25mmol) 2,5-dihydroxyterephthalic acid (DOBDC) were added to a mixed solution consisting of 18mL DMF and 12mL H2O, ultrasonically homogenized, and transferred to a polytetrafluoroethylene-lined autoclave at 120°C for 12h. The reaction product was collected by centrifugation, washed three times with methanol to remove the residual DMF reagent in the pores, and freeze-dried to obtain Cu-MOF-74.

[0037] Preparation of CuO: Cu-MOF-74 was packed into a ceramic crucible with a volume of 25 mL and calcined at 400 °C for 2 h in a muffle furnace at a heating rate of 2 °C / min to obtain CuO.

[0038] Preparation of ZIF-67: Weigh 1.65g 2-methylimidazole and 0.7g Co(NO3)2·6H2O and dissolve them in 50mL methanol by ultrasonic homogenization. Then transfer the 2-methylimidazole solution into the Co(NO3)2·6H2O solution and continue stirring for 4h under magnetic stirring. After stirring, collect the ZIF-67 precipitate by centrifugation and dry it at 60℃ for later use.

[0039] CuO x Preparation of / NiCo-LDH: Weigh xg (x = 0.01, 0.03 and 0.05) CuO and 0.035g ZIF-67 in a beaker containing 25mL of anhydrous ethanol, and mix them uniformly by ultrasonication (solution A). Weigh 0.2386g Ni(NO3)2·6H2O and dissolve it in 5mL of anhydrous ethanol (solution B). Under magnetic stirring, transfer solution B into solution A and stir for 5min. Then, ultrasonicate the uniform mixed solution for 45min. After the ultrasonication is finished, collect the sample by centrifugation, wash the sample twice with 30mL of deionized water, and finally dry it under vacuum at 60℃ to obtain CuO x / NiCo-LDH.

[0040] CuO x / A y Preparation of NiCo-LDH:CuO x / A y Preparation of -NiCo-LDH (A represents organic carboxylic acid, y represents the molar amount of organic carboxylic acid, y = 0.1mmol, 0.2mmol, 0.3mmol, 0.4mmol and 0.5mmol) and CuO 0.03 / NiCo-LDH preparation process is the same, except that in the preparation of CuO x / NiCo-LDH, additional amounts of gallic acid (GA), citric acid (CA) and tartaric acid (TA) were added.

[0041] 2. Catalytic activity study and related structural characterization of each prepared reagent

[0042] 1. Catalytic activity study: Add 2.74 mL of deionized water to a centrifuge tube containing 0.0024 g of NaBH4 and shake thoroughly to dissolve the NaBH4; then add 0.25 mL (2 mmol L -1 )4-NP, shake thoroughly, transfer the resulting homogeneous solution into a cuvette, and finally add 0.01 mL (0.5 mg mL -1 ) catalyst, and the absorbance of the sample was monitored every 2 minutes by UV-2550. The entire reaction was carried out at room temperature in a cuvette with a path length of 10 mm and a volume of 3.5 mL. x / NiCo-LDH and CuO x / A y -NiCo-LDH was tested for stability after 5 cycles. After the first cycle, 10 μL (50 mmol L -1 ) of 4-NP and 0.0024 g of NaBH4, and the same operation was repeated in the remaining cycle tests.

[0043] As the most common reaction model, NaBH4 / 4-NP is usually used to evaluate the catalytic activity of catalysts. In this experiment, the entire catalytic reduction process was carried out in a cuvette of a UV-visible spectrometer, and the absorbance changes of 4-NP during the reaction were recorded at a scan rate of 2.0 in the wavelength range of 500-250nm. Based on this test method, the catalytic performance of the target catalyst and its intermediates was evaluated by reducing 4-NP to 4-AP using excess NaBH4 (the molar ratio of NaBH4 to 4-NP was fixed at 125:1) as a reducing agent at room temperature. The results are shown in Figure 2. Figure 1 and Figure 2 shown. Figure 1 (ae) are NiCo-LDH, CuO and CuO respectively x UV-vis spectra of 4-NP catalytic reduction by NiCo-LDH, where CuO 0.03 / NiCo-LDH has the most outstanding catalytic activity towards 4-NP, while CuO 0.01 / NiCo-LDH is second, CuO 0.05 / NiCo-LDH is closest to CuO. It can be seen that the composite of CuO and NiCo-LDH effectively improves the catalytic performance of CuO on 4-NP. x / NiCo-LDH and its precursors catalyzed the reduction of ln(C t The kinetic relationship between / C0) and reaction time t is Figure 1 (f) shows the excellent catalytic activity for 4-NP again, which verifies that the improved strategy is effective. Since the amount of NaBH4 is in excess of that of 4-NP, it can be considered that the concentration of NaBH4 remains constant during the entire reaction. Therefore, the reaction conforms to the pseudo-first-order kinetic law. From the first-order kinetic equation, it is known that CuO 0.03 / The rate constant of NiCo-LDH is k = 0.2521 min -1 , under the same reaction conditions CuO 0.03 / NiCo-LDH(k=0.2521min -1 ) has a slightly lower catalytic activity towards 4-NP than CuO1 / NiO1 (k = 0.2792 min -1 GA, CA and TA were used to treat CuO 0.03 The catalytic activity test results of / NiCo-LDH after modification are as follows Figure 2 It can be seen that the introduction of organic carboxylic acid can effectively improve the catalytic performance of the target catalyst for 4-NP. The specific order of catalytic activity is: CuO 0.03 / TA 0.3 -NiCo-LDH>CuO 0.03 / CA 0.3 -NiCo-LDH>CuO 0.03 / GA 0.3 -NiCo-LDH>CuO 0.03 / NiCo-LDH, in which CuO 0.03 / TA 0.3 -The rate constant k of catalytic reduction of 4-NP by NiCo-LDH is as high as 0.5357min -1 , is CuO 0.03 / NiCo-LDH is twice as much. It can be seen that organic carboxylic acid plays a vital role in the efficient catalytic reduction of 4-NP by the target catalyst; in addition, the synergistic effect between CuO and NiCo-LDH and the small size of the nano-CuO main body are also the main reasons for the high efficiency of 4-NP reduction. 0.03 / A 0.3 -NiCo-LDH showed excellent catalytic activity for 4-NP. After knowing that organic carboxylic acid can improve the catalytic activity of the target catalyst for 4-NP, CuO 0.03 / TA 0.3 -NiCo-LDH was used as the research object, and the optimal amount of TA was found under the experimental conditions by adjusting the amount of TA. Figure 2 As shown in (cd), the catalytic activity is not positively correlated with the amount of TA, but the catalytic activity is optimal when the amount is 0.3 mmol.

[0044] The NaBH4 / 4-NP reaction model is induced by NaBH4. Because NaBH4 can provide sufficient free electrons and hydrogen sources as an electron donor to form surface active hydrogen species with reductive properties on the surface of the catalyst to convert 4-NP into 4-AP, it plays a crucial and dominant role in the reaction. In addition, the concentration of 4-NP is also an influencing factor that cannot be ignored in this reaction. Therefore, the effect of the amount of NaBH4 and the concentration of 4-NP on the CuO 0.03 / TA 0.3 -Effect of NiCo-LDH on the catalytic reduction activity of 4-NP. Figure 3 (ab) shows the effect of NaBH4 on CuO 0.03 / TA 0.3 -NiCo-LDH catalytic reduction of 4-NP, as the molar ratio of NaBH4 / 4-NP increased from 75:1 to 175:1, CuO 0.03 / TA 0.3 -NiCo-LDH significantly improved the catalytic reduction rate of 4-NP, and the rate constant increased sharply from 0.2895 to 0.7423min -1 However, when the NaBH4 / 4-NP molar ratio was fixed at 125:1 and the 4-NP concentration was controlled as a single variable, the CuO 0.03 / TA 0.3 -The catalytic reduction rate of 4-NP by NiCo-LDH is negatively correlated with the concentration of 4-NP ( Figure 3 (cd)). This is because 4-NP binds to BH4 - There is a competitive relationship between them. High concentration of 4-NP in CuO 0.03 / TA 0.3 -NiCo-LDH surface has stronger affinity and occupies more active sites, and there are not enough active sites for BH4 - According to the Langmuir-Hinshelwood model, only when a considerable amount of binary ions coexist on the surface of the catalyst can the efficient catalytic reduction of 4-NP be achieved. 0.03 / TA 0.3 -The effect of the catalytic reduction ability of NiCo-LDH, it can be seen that the amount of NaBH4 and the concentration of 4-NP have a great influence on the catalytic reduction rate of 4-NP.

[0045] In addition, reaction temperature is also an important factor affecting the catalytic reaction. By changing the reaction temperature from 15℃ to 35℃, the CuO 0.03 / TA 0.3 -Thermodynamic parameters of catalytic reduction of 4-NP by NiCo-LDH. Figure 4(ab) It can be seen that CuO 0.03 / TA 0.3 -NiCo-LDH catalytic reduction activity of 4-NP increases with increasing temperature. Based on this experimental result, the rate constant k at each reaction temperature was substituted into the Arrhenius equation and the Eyring-Polanyi equation to estimate the CuO 0.03 / TA 0.3 -The activation energy of catalytic reduction of 4-NP by NiCo-LDH (E a ) and enthalpy change (ΔH). Figure 4 (c) It is known that CuO 0.03 / TA 0.3 -The activation energy of catalytic reduction of 4-NP by NiCo-LDH is Ea=38.88 kJ mol -1 , between 8.368 and 41.84 kJ mol -1 The range indicates that the reaction is a surface catalytic reaction, that is, the entire reaction process is carried out on the surface of the catalyst. Compared with the activation energy Ea of 61.54 kJ mol for the catalytic reduction of 4-NP by CuO1 / NiO1 in Chapter 2, -1 , indicating that under the same reaction conditions, CuO 0.03 / TA 0.3 -NiCo-LDH catalytic reduction of 4-NP has significantly lower activation energy and higher catalytic activity, which proves that our improved method is reasonable and effective. In addition, the relationship between ln(k / T) and 1 / T ( Figure 4 The slope of (d)) shows that the enthalpy change of the reaction is 36.40 kJ mol -1 .

[0046] The recyclability of the catalyst is an important parameter to evaluate whether the catalyst has practical use value. Excellent recyclability can significantly reduce the cost of industrial wastewater treatment, thereby increasing revenue. Therefore, the Cu O 0.03 / TA 0.3 -The cycling stability of NiCo-LDH is shown in Figure 5 (a) is shown. CuO 0.03 / TA 0.3 After five repeated uses, the catalytic degradation rate of 4-NP by NiCo-LDH did not decrease significantly, which proved that CuO 0.03 / TA 0.3 -NiCo-LDH has good cycle stability. Electrochemical impedance spectroscopy (EIS) is often used to understand the conductivity of a substance. In order to understand the conductivity differences of the target catalyst and its intermediates, impedance test experiments were conducted on them. The Nyquist Diagram of each sample is located at Figure 5(b) CuO has the best catalytic performance 0.03 / TA 0.3 -NiCo-LDH has the smallest arc, CuO 0.03 / NiCo-LDH is second, and the diameter range of the remaining CuO is smaller than that of NiCo-LDH. In the Nyquist spectrum, the smaller the arc, the better the conductivity of the sample, indicating that CuO 0.03 / TA 0.3 -NiCo-LDH has better conductivity than CuO 0.03 / NiCo-LDH, CuO and NiCo-LDH. It can be seen that CuO 0.03 / TA 0.3 -The excellent conductivity of NiCo-LDH is also one of the internal factors that cannot be ignored for its excellent catalytic activity.

[0047] 2. Related structural characterization: Scanning electron microscopy (SEM, ZEISS, Germany), high-resolution transmission electron microscopy (TEM, Tecnai G2 F30 S-TWIN), energy dispersive X-ray spectroscopy (EDS) and element mapping were used to study the morphology, elemental composition and distribution of the materials; high-resolution transmission electron microscopy combined with X-ray powder diffractometer (XRD, HAOYUAN) at a scanning speed of 5° min -1 , scanning range 5-80°, tube voltage 40KV and tube current 30mA were used to analyze the structure of the materials; X-ray photoelectron spectroscopy (XPS, Thermo ESCALAB 250Xi) equipped with Al target was used to analyze the valence state of the elements in the sample, and the charge correction of each element was performed based on the C1s binding energy of 284.8eV; Raman spectrometer (Raman spectrometer, Alpha 300access WITec, Germany) was used to obtain the structural information of the sample with an excitation wavelength of 532nm and a light source size of 1μm. Fourier transform infrared spectrometer (FT-IR) was used to verify whether the material contained corresponding functional groups. The Brunauer-Emmett-Teller (BET) model and Barrett-Joyner-Halenda (BJH) method were used to obtain the specific surface area and pore size distribution information of the sample. Electrochemical impedance spectroscopy (EIS) was performed by a three-electrode system (working electrode: drop-coated with 1×1cm 2The ITO conductive glass of the catalyst slurry, the reference electrode: Ag / AgCl electrode and the counter electrode: Pt electrode) were immersed in 0.2MNa2SO4 solution and the electrochemical impedance spectroscopy was carried out at room temperature using a CHI 660E electrochemical workstation to compare the conductivity differences of the samples; the catalytic performance of the catalyst was monitored in the wavelength range of 500-250nm using an ultraviolet-visible spectrophotometer (SHIMADZU, UV-2550).

[0048] like Figure 6 As shown, Figure 6 (ac) show the CuO at different magnifications. 0.03 / TA 0.3 -The microscopic morphology of NiCo-LDH shows that NiCo-LDH is coated with CuO nanoparticles, with particle sizes ranging from tens to hundreds of nanometers, confirming its nanoscale particle characteristics. The formation of NiCo-LDH on the surface of CuO nanoparticles makes the CuO surface rough and irregular, thereby increasing the specific surface area, generating more active sites and thus enhancing the adsorption of the catalyst on 4-NP. Figure 6 (d) is nano CuO 0.03 / TA 0.3 -The EDS graph of NiCo-LDH shows that the sample contains five elements: C, O, Ni, Co and Cu. Figure 7 As shown, CuO 0.03 / TA 0.3 The element distribution diagram of -NiCo-LDH also shows that C, O, Ni, Co and Cu coexist in the sample and are uniformly distributed in the sample.

[0049] In order to further understand the structure of the target catalyst and its precursor, XRD characterization technology was used to explore the crystal structure of the sample. Figure 8(ac) are shown. First, the XRD spectrum of the obtained ZIF-67 is highly consistent with the results reported in the literature, indicating that a pure ZIF-67 phase was prepared. In addition, NiCo-LDH showed characteristic peaks near 2θ=11.0°, 22.5°, 33.6° and 60.0°, which correspond to the (003), (006), (009) and (110) crystal planes of NiCo-LDH, respectively. This result is consistent with the XRD analysis results of NiCo-LDH reported in the literature, proving that NiCo-LDH was successfully synthesized. Moreover, compared with the standard card PDF#00-045-0937, the strong peaks at 32.43°, 35.46°, 38.68° and 48.84° in the spectrum correspond to the (-110), (11-1), (111) and (20-2) crystal planes of CuO, respectively. Similarly, NiCo-LDH doped with different amounts of CuO was characterized by XRD. The analysis results show that the XRD characteristic peaks of NiCo-LDH can hardly be observed after doping with CuO, because the strong characteristic peaks of CuO cover the characteristic peaks of NiCo-LDH. This phenomenon also exists in the XRD spectra of CuO / NiCo-LDH nanocomposites modified by GA, CA and TA. In order to obtain more composition and structural information of the target catalyst and its precursor, FT-IR tests were carried out on the target catalyst and its precursor. The results are shown in Figure 2. Figure 8 (de) shown. Figure 8 In (d), at low wavenumbers 400-700 cm -1 The strong peak in the interval is the stretching vibration caused by the chemical bond of Cu-O, which confirms that CuO was successfully synthesized. -1 The broad peak centered at 1605 cm -1 The characteristic peak caused by the stretching vibration of -OH in H2O appears at 1365cm -1 In addition, at 645 and 471 cm -1 The characteristic peaks that appeared nearby correspond to the stretching vibrations of Co-O and Ni-O, respectively, which once again verified that NiCo-LDH was successfully synthesized. The infrared spectra of CuO / NiCo-LDH nanocomposites doped with different amounts of CuO also showed characteristic peaks at the corresponding positions, which once again proved that the CuO / NiCo-LDH nanocomposites were successfully prepared. It is worth noting that with the increase of the amount of CuO in the CuO / NiCo-LDH nanocomposites, the intensity of the infrared characteristic peaks of NiCo-LDH gradually weakened. This phenomenon is caused by the relative content of NiCo-LDH in the composite material. 0.03 / TA y-In the infrared spectrum of NiCo-LDH nanocomposite materials, the wave number is 1580cm -1 The asymmetric stretching vibration of -COO- appears near the surface, which is a strong evidence to confirm the successful modification of NiCo-LDH by organic carboxylic acid ( Figure 8 (e)). The molar amount of CuO in this group of samples remains constant. As the amount of organic carboxylic acid increases, the proportion of CuO in the composite material gradually decreases, which also leads to a decrease in the intensity of the infrared characteristic peak of Cu-O.

[0050] XPS characterization technology is mainly used to determine the valence state of elements contained in the sample, CuO 0.03 / TA 0.3 -XPS analysis results of NiCo-LDH are as follows Fig. 9 As shown, the overall spectrum ( Fig. 9 (a)) shows that the sample contains five elements: Cu, Ni, Co, O and C. The XPS spectrum of the C element ( Fig. 9 (b)) has three characteristic peaks, among which the peak at 284.8eV is the contamination carbon correction peak, and the remaining two peaks with binding energies of 286.59 and 288.59eV are the characteristic peaks of CO and C=O, respectively. Fig. 9 (c) It can be seen that O 1s is fitted into three peaks at 529.80, 531.70 and 533.09 eV, among which the characteristic peak at 529.80 eV is related to Cu 2+ Combined lattice oxygen (O L ), while the characteristic peaks located near 531.70 and 533.09 eV are caused by chemically adsorbed oxygen species. Fig. 9 (d) shows the XPS analysis results of Cu 2p. In the Cu 2p spectrum, there is a double peak with binding energies of 934.28 and 953.62 eV, corresponding to Cu 2+ Cu 2p 3 / 2 and Cu 2p 1 / 2 In addition, Cu appeared at 942.64 and 962.55 eV. 2+ The satellite peaks of Ni2p and the analysis results of O1s orbital confirmed that the sample contained CuO phase. Fig. 9 (e)) is divided into two main peaks and two satellite peaks due to spin-orbit splitting. The main peaks centered at 855.88 and 873.99 eV correspond to Ni 2+ Ni 2p 3 / 2 and Ni 2p 1 / 2 orbital, and the remaining two characteristic peaks with binding energies of 861.40 and 879.43 eV are Ni 2+ Satellite peaks of Ni 2p orbitals. High-resolution XPS spectrum of Co 2p ( Fig. 9 (f)) Two strong peaks appeared at 781.17 and 796.81 eV, corresponding to Co 3+ Co 2p 3 / 2 and Co 2p 1 / 2 orbital. In addition, the characteristic peak at 784.48 eV is Co 3+ The satellite peaks also indicate that NiCo-LDH contains Co 3+ The peak centered at 774.62 eV is Co 2+ Satellite peaks of Co 2+ and Co 3+ Coexisting in the sample, Co 3+ Co in ZIF-67 from the coprecipitation process 2+ Oxidized to Co 3+ , confirming that NiCo-LDH was successfully synthesized.

[0051] In addition, the specific surface area of ​​CuO 0.03 / TA 0.3 -Specific surface area and pore size distribution of NiCo-LDH and its precursor. The results are as follows Fig.10 As shown. Based on the N2 adsorption and desorption isotherm curve ( Fig.10 (a) CuO 0.03 / NiCo-LDH, NiCo-LD H and CuO all have type IV isotherms with H3 hysteresis loops, while TA 0.3 / NiCo-LDH and CuO 0.03 / TA 0.3 -NiCo-LDH is a type IV isotherm with an H2 hysteresis loop. From the analysis report, we can see that the order of specific surface area of ​​each sample is: NiCo-LD H (66.65m 2 / g)>CuO 0.03 / NiCo-LDH(30.46m 2 / g)>CuO(14.95m 2 / g)>CuO 0.03 / TA 0.3 -NiCo-LD H(8.92m 2 / g)>TA 0.3 / NiCo-LDH(0.97m 2 / g). It can be seen that CuO 0.03 / NiCo-LDH and CuO 0.03 / TA 0.3 -NiCo-LDH's specific surface area did not increase but decreased, which may be due to the fact that the surface and pores of the material were occupied due to the synthesis method. At the same time, the pore size distribution curves of each sample are located at Fig.10(b), CuO 0.03 / TA 0.3 -NiCo-LDH, CuO 0.03 / NiC o-LDH、TA 0.03 The average pore sizes of BJH adsorption of / NiCo-LDH, NiCo-LDH and CuO are 8.66nm, 17.63nm, 24.50nm, 16.66nm and 24.85nm, respectively.

[0052] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.

Claims

1. An organic acid-modified 4-NP reaction catalyst, characterized in that: CuO, ZIF-67 and nickel nitrate in a mass ratio of 1:1.16:7.95 are used as preparation raw materials, anhydrous ethanol is used as solvent, substance A is introduced in the preparation process, and the substance A is tartaric acid. The CuO-A-NiCo-LDH obtained by ultrasound assistance is the 4-NP reaction catalyst, wherein the molar ratio of tartaric acid to CuO is 1:1.

25.

2. The method for preparing an organic acid-modified 4-NP reaction catalyst according to claim 1, characterized in that: The steps include: (1) CuO and ZIF-67 were placed in a beaker containing anhydrous ethanol, and ultrasonically homogenized to obtain a solution 1 for later use; (2) Ni(NO3)2·6H2O is placed in anhydrous ethanol to obtain solution 2 for later use; (3) Under stirring, solution 2 is transferred into solution 1, and tartaric acid is added. After stirring evenly, ultrasonic treatment is performed for 30 to 60 minutes. After the ultrasonic treatment is completed, the sample is collected by centrifugation, washed with deionized water, and finally vacuum dried to obtain CuO-A-NiCo-LDH.

3. The method for preparing the organic acid-modified 4-NP reaction catalyst according to claim 2, characterized in that: The preparation process of the CuO is as follows: adding Cu(Ac)2·H2O and 2,5-dihydroxyterephthalic acid in a molar ratio of 1.5:1 to a mixed solution of DMF and H2O in a volume ratio of 1.5:1, ultrasonically homogenizing, reacting at 100-150°C for 10-24h, collecting the product after the reaction by centrifugation, washing with methanol and freeze-drying, and then calcining the dried product at 400-450°C for 1-4h to obtain CuO.

4. The method for preparing the organic acid-modified 4-NP reaction catalyst according to claim 3, characterized in that: The calcination was carried out in a muffle furnace, and the temperature rise rate in the muffle furnace was 2°C / min.

5. The method for preparing the organic acid-modified 4-NP reaction catalyst according to claim 2, characterized in that: The preparation process of ZIF-67 is as follows: 2-methylimidazole and Co(NO3)2·6H2O are dissolved in methanol respectively and ultrasonically homogenized, then the 2-methylimidazole solution is transferred into the Co(NO3)2·6H2O solution, and after continuous stirring for 4 hours, the ZIF-67 precipitate is collected by centrifugation and dried to obtain ZIF-67.

6. The method for preparing the organic acid-modified 4-NP reaction catalyst according to claim 5, characterized in that: The mass ratio of the 2-methylimidazole to Co(NO3)2·6H2O is 2-2.5:

1.

7. Use of the organic acid-modified 4-NP reaction catalyst according to claim 1 in catalytic decomposition of 4-NP, characterized in that: The reaction uses NaBH4 as the reducing agent.